LAUDATO SÍ: A REFLECTIVE SUMMARY - Kevin Kelly (Asian Horizons, 2015)
In Laudato Sí Francis insists our Christian faith is ‘heart’ knowledge more than ‘head’ knowledge. This article contains a summary of Francis’s 2015 Encyclical, ‘Laudato Sí based on the reported comments of various writers and concluding with a summary of the Declaration of Islamic leaders on Climate Change and Ecology (Istanbul, 18/8/15) as reported in the National Catholic Reporter, 19/8/15